KOMUNIKASI KELOMPOK PENDAKI GUNUNG KOMUNITAS KONCO STREET PAYAKUMBUH DALAM MENJALIN SOLIDARITAS - Kurnia, Vina; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Konco Street is a family-based mountaineering community that emphasizes solidarity. This community has members with a variety of different backgrounds. The interesting thing about this community is that the members only consist of men, climbing at minimal costs and visiting hidden places that are rarely visited such as waterfalls, lakes and so on. other. The research was conducted in Payakumbuh in the Konco Street mountain climber community. The aim of this research is to find out: 1) the role of group communication members in the Konco Street group communication of the Payakumbuh Mountain Climber Community in establishing solidarity 2) the function of group communication in the Konco Street community 3) communication patterns that occur in the group communication process in the Konco Street Payakumbuh community . This research uses descriptive qualitative research methods. This research uses purposive and incidental subject determination techniques and uses interview, observation and documentation data collection techniques. The data analysis technique used is the Miles and Huberman technique which consists of data collection, data reduction, data presentation and verification. The data validity checking technique uses the Triangulation technique. The results of this research show that the role of the leader in the group is as a decision maker, mediator when conflict occurs between members, and as a supporter for members both for activities and to maintain solidarity between members. Management in the Konco Street community plays a role in carrying out their respective functions in accordance with the established management structure. In maintaining community solidarity, not only the chairman plays a role, but the management and members also play a big role in this matter. The function of group communication that occurs in the Konco Street community is the function of social relations, the function of education and the function of preliminary solving. The pattern used in Konco Street community group communication is the star pattern where communication occurs in all directions. Every member is free to communicate with anyone without the need for intermediaries.